2005
DOI: 10.1080/10715760500143478
|View full text |Cite
|
Sign up to set email alerts
|

Free radical mediated oxidative stress and toxic side effects in brain induced by the anti cancer drug adriamycin: Insight into chemobrain

Abstract: Adriamycin (ADR) is a chemotherapeutic agent useful in treating various cancers. ADR is a quinone-containing anthracycline chemotherapeutic and is known to produce reactive oxygen species (ROS) in heart. Application of this drug can have serious side effects in various tissues, including brain, apart from the known cardiotoxic side effects, which limit the successful use of this drug in treatment of cancer. Neurons treated with ADR demonstrate significant protein oxidation and lipid peroxidation. Patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 51 publications
7
106
0
4
Order By: Relevance
“…Postulated explanations are enhanced neural cell death and decreased cell division [28], due to crossing of the bloodbrain barrier by certain chemotherapeutic agents and increased levels of oxidative stress [29]. Cell death however is less likely to explain the smaller volume, since it is considered irreversible and therefore contradictive to the partial recovery of local gray matter reductions that were reported in a longitudinal study after the effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Postulated explanations are enhanced neural cell death and decreased cell division [28], due to crossing of the bloodbrain barrier by certain chemotherapeutic agents and increased levels of oxidative stress [29]. Cell death however is less likely to explain the smaller volume, since it is considered irreversible and therefore contradictive to the partial recovery of local gray matter reductions that were reported in a longitudinal study after the effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…MRP1 has an unusually broad substrate specificity and can transport not only hydrophilic compounds such as GSH conjugates but also numerous hydrophobic compounds including therapeutic drugs (Loscher and Potschka, 2005b). Additionally, it has been reported that a chemotherapeutic agent affects MRP1 expression in the mice brain (Joshi et al, 2005). Therefore, the in vivo quantitative assessment of brain MRP1 function is useful for examining the alteration of MRP1 related to brain diseases and for directly evaluating the effect on MRP1 caused by drugs including modulators used to improve brain drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heavy metals induce oxidative stress by generation of hydrogen peroxide, superoxide radical, hydroxyl radical and singlet oxygen, collectively termed reactive oxygen species (ROS) (Verma and Dubey, 2003). Many organic molecules are exposed to severe damage by free radicals after high accumulation of heavy metals in plants (Alfonso and Puppo, 2009;Joshi et al, 2005). Formation of ROS in cells is associated with the development of many pathological states (e. g. reduced root elongation, seed germination, signaling imbalance) (Bini et al, 2008;Wahsha and Al-Jassabi, 2009).…”
Section: Introductionmentioning
confidence: 99%